2010
DOI: 10.5194/acpd-10-20239-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An analysis of the Collection 5 MODIS over-ocean aerosol optical depth product for its implication in aerosol assimilation

Abstract: As an update to our previous use of the Collection 4 Moderate Resolution Imaging Spectroradiometer (MODIS) over-water aerosol optical depth (AOD, symbol as τ data, we examined ten years of Terra and eight years of Aqua data Collection 5 data for its potential usage in aerosol data assimilation. Uncertainties in the over-water MODIS AOD were studied as functions of observing conditions, such as surface characteristics, aerosol optical properties, and cloud artifacts. Empirical corrections and quality assurance … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…However, a few studies have shown that uncertainties still exist in current satellite aerosol products attributable to the complex surface, cloud contamination, and aerosol models used in the retrieving process (e.g. Zhang and Reid, 2006;Zhang et al, 2005;Kahn et al, , 2009Shi et al, 2010;. Those studies also suggested one must be wary of mistakenly interpreting noises and biases in satellite aerosol products as legitimate signals, particularly in demanding application such as data assimilation and long term trend analyses.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a few studies have shown that uncertainties still exist in current satellite aerosol products attributable to the complex surface, cloud contamination, and aerosol models used in the retrieving process (e.g. Zhang and Reid, 2006;Zhang et al, 2005;Kahn et al, , 2009Shi et al, 2010;. Those studies also suggested one must be wary of mistakenly interpreting noises and biases in satellite aerosol products as legitimate signals, particularly in demanding application such as data assimilation and long term trend analyses.…”
Section: Introductionmentioning
confidence: 99%
“…The DA quality MODIS data were created after extensive quality assurance procedures for removing possible cloud contamination, empirical corrections for wind to minimize the uncertainties from surface conditions, and aerosol micro-physical corrections based on derived fine mode fraction. Originally developed for MOD04 data collection 4, minor alterations to the correction coefficients have been made for data collection 5 (Shi et al, 2010). Currently the total global data loss through screening is 24-26%, with a reduction of absolute errors of 10-30% (e.g.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations